George Woods and the World Bank - Oliver, Robert W. (Lynne Rienner, 1995)
George Woods transformed the World Bank from a relatively passive investment organization into an active leader of world development. He pushed for greatly increased lending in support of agriculture and education, worked closely with the United Nations, and revived and greatly strengthened economic analysis in the Bank itself. He also initiated measures to expand the equity investments of the International Finance Corporation and sought annual funding of one billion dollars for the International Development Association, the Bank's soft-loan affiliate. He retired in 1968 after inducing Robert McNamara to be his successor.
Keywords: Woods, George <1901-1982>; Woods, George D.; Woods, George D. -- 1901-; World Bank - History - 20th century; World Bank -- Presidents -- Biography; World Bank -- History -- 20th century; Weltbank; Geschichte 1900-2000; Geschichte 1963-1968; Ontwikkelingsbanken; Wereldbank; Geschichte; Biografie